Reproductive response of goats to different oestrus synchronisation protocols and their combination with fixed time artificial insemination - Mohamad Salleh, Suraya (2014)
There is lack of information on the effects of oestrus synchronisation using Controlled Internal Drug Release (CIDR) insert in goats in Malaysia. Understanding the effect of oestrus synchronisation would enable the use of fixed-time artificial insemination (FTAI), which might increase the efficiency of goat production. This study will determine the most suitable oestrus synchronisation protocol and FTAI to be practiced in goat industries in Malaysia. Two experiments were conducted in this study. In the first experiment, 23 Saanen crossbred does (2 to 4 years old) were divided unequally into 3 groups. The first group received CIDR for 14 days, Pregnant Mare Serum Gonadotrophin (PMSG) and cloprostenol at CIDR removal (CIDR14++; n=8); the second group of does received CIDR for 9 days and PMSG and cloprostenol at CIDR removal (CIDR9++; n=8) and the third group received CIDR for 9 days and cloprostenol only at CIDR removal (CIDR9+; n=7). Oestrus signs were recorded and blood samples for progesterone (P4) and luteinising hormone (LH) analysis were collected for 24 h at 4 h interval, starting from 24 h post CIDR removal. Data on oestrus signs, P4 and LH were analysed using one-way ANOVA. Results showed 100 % of does in group CIDR14++ in oestrus, while the other two groups (CIDR9++ and CIDR9+) showed only 57% and 33 %, respectively. The time from CIDR removal until onset of oestrus in CIDR9+ was significantly longer (P<0.05) than CIDR9++ and CIDR14++. The P4 concentration at 24 h post CIDR removals decreased when compared with P4 levels at CIDR removal in all groups. The LH concentration at peak (8.03±2.07 mIU/ml) for CIDR14++ was significantly higher (P<0.05) than CIDR9+ (7.32±1.07 mIU/ml) and CIDR9++ (4.94±0.80 mIU/ml). The LH peak occurred at 42.0±1.15, 41.0±1.91 and 43.0±1.00 h post CIDR removal for CIDR14++, CIDR9++ and CIDR9+, respectively. The result from this study suggested that the duration of CIDR treatment could be reduced from 14 to 9 days suitable time to conduct fixed-time artificial insemination (FTAI) in goat is at 55 to 66 h after CIDR removal. In the second experiment, 127 Boer does were divided into three groups and inserted with CIDR intravaginally for 14 (CIDR14++; n=42; CIDR14+; n=42) and 9 days (CIDR9++; n=43). Approximately 0.5 ml PG was administered intramuscularly to all groups at CIDR removal and only groups CIDR14++ and CIDR9++ were administered with 200 IU of PMSG intramuscularly. Does in each oestrus synchronisation protocol were further randomly divided into two subgroups, go through FTAI at either at 55 or 66 h post CIDR removal. The time of AI was chosen based on the results from experiment 1. Oestrus signs were observed at 4 h intervals and blood samples were collected for P4 and LH determination. The number of does pregnant was determined by ultrasonography at 30 days post AI. Data on oestrus observations, P4 and LH were analysed using Chi-square and GLM by SAS 9.3 software. The percentage of does in oestrus within 24 to 72 h post CIDR removal were significantly higher (P<0.05) in groups CIDR14++ (97.6%) and CIDR 9++ (100%) compared to group CIDR14+ (81.0%). The numbers of does displaying oestrus signs within 24 to 28 h post CIDR removal were significantly higher (P<0.05) in group CIDR9++ compared to groups CIDR14++ and CIDR14+. The P4 concentrations at 24 hours post CIDR removals and LH concentration were not significantly different (P>0.05) in all groups. The time of LH peak in group CIDR14+ was significantly delayed (P<0.05) when compared to group CIDR9++. The pregnancy rate of FTAI does was not significantly different (P<0.05). In conclusion, the suitable oestrus synchronisation protocols for goat in Malaysia were CIDR14++ and CIDR9++. It is recommended to use the treatment CIDR9++, since the oestrous cycle can be shortened. Since the pregnancy rate in this study is very low; the suitable time to conduct fixed-time AI cannot be concluded.